Collaborative Governance dalam Relaksasi Pemungutan Pajak Bumi dan Bangunan Bagi Wajib Pajak Terdampak Pandemi Covid-19 di Kota Bekasi - Annysa Subagyo; Nurliah Nurdin; Ratri Istania; M. Raihan Geminirwana (Syntax Corporation, 2023)
This study aims to analyze the factors that cause collaborative governance in relaxing UN collection for taxpayers affected by COVID-19 in Bekasi City which has not run well and optimally. The research method used in this study is a mixed method, which is a research approach model that combines a qualitative approach and a quantitative approach. As a result, efforts that can be made so that collaborative governance in relaxing the collection of land and building taxes for taxpayers affected by Covid-19 in the City have not run well and optimally, namely providing an understanding of the benefits of UN payments that return to the community, conducting socialization through various online and offline payment media, building good cooperation with stakeholders, create institutional designs that regulate cooperation through Cooperation Agreements (PKS) between stakeholders, conduct face-to-face dialogue on an ongoing basis involving all stakeholders, create tiered communication forums and conduct monitoring and evaluation to ensure the implementation of collaborative governance in relaxing UN collection for taxpayers affected by COVID-19 in Bekasi City runs well and optimally and achieves the UN revenue target Set. In conclusion, collaborative governance in relaxing the collection of land and building taxes for taxpayers affected by COVID-19 in the City has not run well and optimally, namely in the initial conditions, facilitative leadership, institutional design, face-to-face collaboration process, collaborative process of mutual understanding and collaboration process of temporary results. While in the collaboration process building trust and the collaboration process, commitment to the process has run well